Successful outcomes with oral fluoroquinolones combined with rifampicin in the treatment of Mycobacterium ulcerans: an observational cohort study. - Daniel P O'Brien; Anthony McDonald; Peter Callan; Mike Robson; N Deborah Friedman; Andrew Hughes; Ian Holten; Aaron Walton; Eugene Athan (Public Library of Science (PLoS), 2012)
BACKGROUND: The World Health Organization currently recommends combined streptomycin and rifampicin antibiotic treatment as first-line therapy for Mycobacterium ulcerans infections. Alternatives are needed when these are not tolerated or accepted by patients, contraindicated, or neither accessible nor affordable. Despite in vitro effectiveness, clinical evidence for fluoroquinolone antibiotic use against Mycobacterium ulcerans is lacking. We describe outcomes and tolerability of fluoroquinolone-containing antibiotic regimens for Mycobacterium ulcerans in south-eastern Australia. METHODOLOGY/PRINCIPAL FINDINGS: Analysis was performed of prospectively collected data including all primary Mycobacterium ulcerans infections treated at Barwon Health between 1998 and 2010. Medical treatment involved antibiotic use for more than 7 days; surgical treatment involved surgical excision of a lesion. Treatment success was defined as complete lesion healing without recurrence at 12 months follow-up. A complication was defined as an adverse event attributed to an antibiotic that required its cessation. A total of 133 patients with 137 lesions were studied. Median age was 62 years (range 3-94 years). 47 (34%) had surgical treatment alone, and 90 (66%) had combined surgical and medical treatment. Rifampicin and ciprofloxacin comprised 61% and rifampicin and clarithromycin 23% of first-line antibiotic regimens. 13/47 (30%) treated with surgery alone failed treatment compared to 0/90 (0%) of those treated with combination medical and surgical treatment (p<0.0001). There was no difference in treatment success rate for antibiotic combinations containing a fluoroquinolone (61/61 cases; 100%) compared with those not containing a fluoroquinolone (29/29 cases; 100%). Complication rates were similar between ciprofloxacin and rifampicin (31%) and rifampicin and clarithromycin (33%) regimens (OR 0.89, 95% CI 0.27-2.99). Paradoxical reactions during treatment were observed in 8 (9%) of antibiotic treated cases. CONCLUSIONS: Antibiotics combined with surgery may significantly increase treatment success for Mycobacterium ulcerans infections, and fluoroquinolone combined with rifampicin-containing antibiotic regimens can provide an effective and safe oral treatment option.